(untitled) (Jurnal Bahasa, 2019)
Giongo (擬音語) is the term for onomatopoeic words used to imitate sound or voice, while gitaigo (擬態語) is the term for words that mimic an act, condition or behaviour that does not produce sound in a manga. Although studies on giongo and gitaigo have been conducted by researchers abroad, research on the translation procedures of giongo and gitaigo has so far not been conducted in Malaysia. In this regard, this study aims to examine the translation procedures of giongo and gitaigo in the manga Kimi no Na wa from Japanese into Malay. In this study, content analysis is performed to identify giongo and gitaigo in manga based on Natsume’s (1997) view. The analysis of the translation procedures is carried out based on the comic or manga translation procedures proposed by Kaindl (1999). The study found that giongo and gitaigo in manga can be categorized into ’giongo/gitaigo without speech bubbles’ and ’giongo in speech bubbles’. The findings also show that giongo/gitaigo without speech bubbles in the texts studied can be translated using seven procedures, while giongo in speech bubbles are translated using two procedures. The translation procedures identified show similarities with the translation procedures found in previous studies of other language pairs than Japanese and Malay. The study also identified translation procedures that are specifically adopted in the Malaysian context. Keywords: translation procedure, giongo, gitaigo, manga